HEPATOPROTECTIVE EFFECT OF FOREST HONEY ON CARBON TETRACHLORIDE INDUCED FEMALE WISTAR RATS - Yunita Linawati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
Hepatoprotective effect study of forest honey had been conducted on a female rat induced with carbon tetrachloride (CCl4). The study aimed at obtaining the scientific data and the evidence of forest honey as hepatoprotective agent on the rat. The study was a true experimental study with a single factor completely randomized design. Thirty rats were randomly divided into six groups (n=5). Group I received carbon tetrachloride 2.0 mL/kgBW intraperitoneally, group II received olive oil 2.0 mL/kgBW intraperitoneally, group III received forest honey 8.1 mL/kgBW (6 days, peroral), groups IV, V, VI were given forest honey 3.6, 5.4, 8.1 mL/kgBW (6 days, peroral) and intraperitoneal induction of carbon tetrachloride 2 mL/kgBW on seventh day. The blood sample of all rats were taken for ALT-AST measurement and their liver were sampled for histological examination of the liver cell. Groups I and III on the seventh day, group II on the second day, groups IV,V,VI on the eighth day. The result showed that a forest honey can be used as a hepatoprotective agent on the female rat Wistar strain induced by carbon tetrachloride 2 mL/kgBW with doses 3.6, 5.4, 8.1 mL/kgBW.